2015
DOI: 10.1080/00221341.2015.1070366
|View full text |Cite
|
Sign up to set email alerts
|

Gods of the City? Reflecting on City Building Games as an Early Introduction to Urban Systems

Abstract: For millions of gamers and students alike, city building games (CBGs) like SimCity and the more recent Cities: Skylines present a compelling initial introduction to the world of urban planning and development. As such, these games have great potential to shape players' understanding and expectations of real urban patterns and processes. In this article I argue that, despite the fundamental role of agency in CBGs and other sandbox type games, players are constrained by the developers' assumptions and biases reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…However, from an educational perspective, this approach also has to be discussed critically, as every selection/limitation implies the risk of being biased. As Bereitschaft [8] (p. 51) noted in his analysis of city building games, "players are constrained by the developers' assumptions and biases regarding how cities ought to look and function". According to Bereitschaft city building games, for instance, "emphasize personal transportation over transit" [8] (p. 51) and the development of a large number of measures needed to create a sustainable city in Cities: Skylines cannot be implemented without the Green Cities DLC.…”
Section: Curation Of the Scope Of Possibilities (Possible Decisions)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, from an educational perspective, this approach also has to be discussed critically, as every selection/limitation implies the risk of being biased. As Bereitschaft [8] (p. 51) noted in his analysis of city building games, "players are constrained by the developers' assumptions and biases regarding how cities ought to look and function". According to Bereitschaft city building games, for instance, "emphasize personal transportation over transit" [8] (p. 51) and the development of a large number of measures needed to create a sustainable city in Cities: Skylines cannot be implemented without the Green Cities DLC.…”
Section: Curation Of the Scope Of Possibilities (Possible Decisions)mentioning
confidence: 99%
“…The use of games to teach decision-making-as part of complex problem-solving relevant for geography education-is supported by, at least, four main arguments. First, numerous studies have shown the potential of digital games-both serious and entertainment games-as a tool for education in general [3][4][5], and geography education in particular [6][7][8][9]. Second, a lot of strategy and management games refer to problems discussed in geography education and also arrange these problems in a spatial way.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by the time-series mean values, decreasing and increasing trends can be observed for BCR and FAR, respectively, which is partly due to the replacement of compact low-rise building areas with open high-rise ones (Figure 9a), as mentioned in Sections 3.2 and 3.3. Meanwhile, urban redevelopment has been dedicated to optimizing land-use structure, in order to mitigate the "big city diseases" [74]. For example, as shown in Figure 9b,d, areas with high building density have been redeveloped to urban green spaces, leading to an inevitable decrease of BCR and a possible increase of FAR.…”
Section: Change Analysis Of the Urban Functional Zonesmentioning
confidence: 99%
“…When considering flagship smart city architectures, then, it becomes clear that spaces such as the GOC and the Data Dome are imbued with a videological approach to the city that is, at heart, also a ludic approach rooted in the aesthetics of videogaming. This is because the screens and consoles, and the potential for visualisations of both data and physical spaces of the city, render the smart city operative as a 'gamer' who can direct, control (play) the city much as a videogamer can be absorbed in an urban simulation like the popular SimCity videogame (Bereitschaft, 2016).…”
Section: Analysing Flagship Smart Urban Spacesmentioning
confidence: 99%